STRATEGI DAN KONSEP PENGENDALIAN INTERNAL PADA OT GROUP - Lukman Surjadi (Jurnal Serina Ekonomi dan Bisnis, 2023)
The purpose of this study is to analyze how from a problem can analyze from the control carried out by theOT Group. In this topic, will discuss about the factors that can af ect internal control itself, its objectives,components, to "The Sarbanes-Oxley Act (SOX) of 2002". This research is supported by national andinternational journals, international articles, as well as literature from libraries. The findings are that thereare many kinds that can be implemented in the field, but they must also have risks and impacts that arethought of on the board of commissioners, management, and personnel within the OT Group. The mainobjective of the author is to explore on internal control itself and what makes internal control itself formed,if drawn an example is COSO (Committee of Sponsoring Organizations of the Treadway Commission).